An Analysis of ACRS during Inflationary Periods - Swenson, Charles W. (The Accounting Review, 1987)
[The neutrality and equity aspects of the Accelerated Cost Recovery System (ACRS), which became part of the U.S. tax law in 1981, are examined using a Monte Carlo simulation. ACRS depreciation is found to be equivalent to general price-level adjusted (GPL) depreciation only at inflation rates of between nine and 13 percent. To the extent that corporations alter their production, investment, and financing activities as a result of inflationary misstatement, the post-1980 law is nonneutral during times of inflation. Further, ACRS will result in a substantial, disproportionate relative capital shift among industries during inflationary periods, which indicates the horizontal inequity of the post-1980 law. This capital shift will be largest for capital-intensive industries having long-lived assets, such as transportation, utilities, and real estate. Both nonneutrality and horizontal inequity lead to decreased economic efficiency and a deadweight loss to the economy.]